A Fe-Mn-Al-C series lightweight high-strength steel and preparation method thereof
By adding specific elements to the Fe-Mn-Al-C lightweight high-strength steel and using laser selective melting (SLM) preparation technology, the problems of the steel in the prior art during processing are solved, and high-efficiency forming and high-performance lightweight high-strength steel are achieved.
Patent Information
- Application Number
- CN202410673812.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-28
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-05-28
AI Technical Summary
The existing Fe-Mn-Al-C lightweight high-strength steel is difficult to process during forging and rolling, is prone to cracking, has a long processing cycle, is low production efficiency, and is difficult to prepare parts with complex structures.
Laser selective melting (SLM) preparation technology is used to prepare high-quality alloy powders by adding elements such as Al, C, Mn and Ni, combined with vacuum smelting-plasma rotary atomization method, and SLM process parameters are optimized for 3D printing and stress-resistance annealing.
The high density and crack-free forming of Fe-Mn-Al-C-type lightweight high-strength steel is achieved, which improves its strength and wear resistance, and has the forming ability of complex special-shaped structures and the forming performance of high melting point materials.
Smart Images

Figure CN118600329B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lightweight high-strength steel, and in particular to a Fe-Mn-Al-C lightweight high-strength steel based on selective laser melting (SLM) preparation technology and a preparation method thereof. Background Art
[0002] At present, the preparation method of Fe-Mn-Al-C series lightweight high-strength steel usually adopts induction melting or arc melting, and then solidification casting, hot processing (forging, rolling) and other processes are processed into final finished parts. Due to the high Al content and C content in Fe-Mn-Al-C series lightweight high-strength steel, it is extremely difficult to process and easy to crack during forging and rolling, with a long processing cycle and low production efficiency. In addition, many parts with complex structures in the fields of aviation, automobile manufacturing, and chemical industry are difficult to prepare, and traditional preparation methods have great limitations. Therefore, Fe-Mn-Al-C series lightweight high-strength steel urgently needs a preparation method with high forming efficiency, high material utilization, low cost, and strong forming ability of complex special-shaped structures and high melting point materials. Summary of the invention
[0003] In order to overcome the deficiencies of the prior art, one of the objectives of the present invention is to provide a Fe-Mn-Al-C series lightweight high-strength steel to solve the above-mentioned traditional technical problems.
[0004] A second object of the present invention is to provide a method for preparing the above-mentioned Fe-Mn-Al-C series lightweight high-strength steel.
[0005] One of the purposes of the present invention is achieved by the following technical solution:
[0006] A Fe-Mn-Al-C series lightweight high-strength steel, comprising the following components calculated by mass percentage:
[0007] Mn 27-30wt%; Al 8.0-10.0wt%; C 0.9-1.2wt%; Ni 2.5-3.5wt%; the rest is Fe;
[0008] Among them, the Fe-Mn-Al-C lightweight and high-strength steel is prepared by selective laser melting (SLM) preparation technology.
[0009] That is, the present invention can reduce the density of Fe-Mn-Al-C lightweight steel by adding Al element. This is because the density of Al atoms is much lower than that of Fe atoms. Replacing Fe atoms with a part of Al atoms can reduce the density of steel. In addition, the addition of Al element causes lattice expansion, which increases the volume of lightweight steel and further reduces the density. The addition of C element can improve the stability of austenite in steel and the recovery power of austenite, expand the austenite phase area, and have an interstitial solid solution strengthening effect, thereby improving the strength and toughness of Fe-Mn-Al-C lightweight steel. It can also be dissolved in austenite to improve the wear resistance of steel. The addition of Mn element can expand the austenite phase area, increase the stability of austenite, and can stably exist at room temperature. In addition, Mn atoms have a solid solution strengthening effect. In the present invention, the contribution of each element to the density of lightweight steel is, by mass percentage, for every 1% of Al added, the density of steel decreases by 0.101g / cm 3 , can reduce weight by 1.3%; for every 1% addition of C, the density of steel decreases by 0.41g / cm 3 , can reduce weight by 5.2%; for every 1% addition of Mn, the density of steel decreases by 0.0085g / cm 3 , which can reduce weight by 0.1%. The Ni element is added because Ni and Fe are infinitely solid-dissolved, and the Ni element can expand the austenite phase region. It is an element that forms and stabilizes austenite. Therefore, adding the ablation-resistant element Ni to the Fe-Mn-Al-C low-density steel can further improve its ablation resistance and mechanical properties. Then, through the laser selective melting (SLM) preparation technology used in the present invention, the Fe-Mn-Al-C low-density steel has both reduced density and increased strength.
[0010] Furthermore, the Fe-Mn-Al-C series lightweight high-strength steel includes the following components calculated by mass percentage:
[0011] Mn 27-30wt%; Al 8.0-10.0wt%; C 0.9-1.2wt%; Ni 3.25-3.28wt%; the rest is Fe.
[0012] Furthermore, the Fe-Mn-Al-C series lightweight high-strength steel includes the following components calculated by mass percentage:
[0013] Mn 28-29wt%; Al 9.2-9.4wt%; C 0.9-1.0wt%; Ni 3.25-3.28wt%; the rest is Fe. Further, the Fe-Mn-Al-C series lightweight high-strength steel also includes the following components calculated by mass percentage:
[0014] Cr≤0.54wt%; O≤0.019wt%; P≤0.010wt%; S≤0.0047wt%; Si≤0.088wt%; N≤0.0018wt%.
[0015] Furthermore, the properties of the Fe-Mn-Al-C lightweight high-strength steel are as follows: the density of the formed part is 99.6%, there are no defects such as cracks, the Vickers hardness can reach 280Hv, the tensile strength can reach 1100MPa, the yield strength can reach 850MPa, and the elongation after fracture exceeds 35%.
[0016] The second object of the present invention is achieved by adopting the following technical solution:
[0017] A method for preparing Fe-Mn-Al-C series lightweight high-strength steel comprises the following preparation steps:
[0018] S1: Prepare raw materials according to the designed ratio;
[0019] S2: High-quality lightweight high-strength steel alloy powder is produced by vacuum melting-plasma rotary atomization technology, and the lightweight high-strength steel alloy powder with the particle size required for SLM is obtained by screening;
[0020] S3: After optimizing the selective laser process parameters, 3D printing is performed by the selective laser melting forming equipment to obtain highly dense, crack-free, deposited SLM lightweight high-strength steel alloy parts;
[0021] S4: Stress relief annealing is performed on the deposited SLM lightweight high-strength steel parts to obtain SLM lightweight high-strength steel alloy parts with high strength and plasticity.
[0022] Furthermore, in step S2, the particle size of the lightweight high-strength steel alloy powder suitable for the particle size required by SLM is between 15-53 μm, and there is no hollow powder satellite powder.
[0023] Furthermore, in step S3, the specific steps of optimizing the process parameters of the selective laser melting are as follows:
[0024] (1) Dry the powder before printing in a vacuum drying oven for 3-5 hours at a temperature of 75-85°C;
[0025] (2) Inert gas (high-purity argon) is introduced into the molding chamber before printing, and the oxygen concentration is below 300 ppm;
[0026] (3) Raise the substrate temperature to 150-200°C before printing;
[0027] (4) When printing, the enhanced parameters are set, and the first two layers are scanned twice each, and each layer thereafter is scanned once for selective laser melting printing; the process parameters of selective laser melting are: laser power: 90-150 W; scanning speed: 600-1000 mm / s; scanning spacing: 70-90 μm; powder thickness: 20-40 μm; and the scanning strategy is checkerboard scanning.
[0028] Furthermore, in step S4, the specific operation of stress relief annealing is: at 500° C.-600° C., keeping warm for 2-6 hours, and furnace cooling.
[0029] Compared with the prior art, the present invention has the following beneficial effects:
[0030] 1. The Fe-Mn-Al-C lightweight high-strength steel of the present invention reduces the Al content and C content, adds Mn and Ni and other elements, and then cooperates with the laser selective melting (SLM) preparation technology to make the Fe-Mn-Al-C low-density steel both reduce the density and improve the strength. The formed parts of the Fe-Mn-Al-C lightweight high-strength steel have a density of 99.6%, no defects such as cracks, Vickers hardness up to 280Hv, tensile strength up to 1100MPa, yield strength up to 850MPa, and elongation after fracture exceeding 35%.
[0031] 2. The present invention adopts the selective laser melting technology (SLM) to prepare Fe-Mn-Al-C lightweight high-strength steel, which is very challenging. On the one hand, due to the high aluminum content in the alloy, the alloy itself has high thermal conductivity, high reflectivity and low laser absorption rate. During the SLM forming process, the laser energy is easily transmitted and consumed along the substrate, and the powder is not completely melted / solidified. During the solid-liquid transition process, obvious shrinkage deformation occurs, and large thermal stress accumulates in the formed part, causing the formed part to deform or even crack. On the other hand, the rapid energy transfer during the SLM forming process causes the molten pool temperature to decrease, the melt viscosity to increase, the fluidity to decrease, and it is difficult to effectively wet the matrix material, resulting in a spheroidization effect and defects such as internal pores and cracks during forming. At the same time, the rapid melting cooling and repeated remelting unique to the SLM technology can easily produce large residual stresses. The present invention achieves a density of 99.6% of the formed parts without defects such as cracks by preparing high-quality SLM powder and optimizing SLM process parameters. The Vickers hardness can reach 280Hv, the tensile strength can reach 1100MPa, the yield strength can reach 850MPa, and the elongation after fracture exceeds 35%. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 The particle size distribution diagram of the lightweight high-strength steel alloy powder of the embodiment;
[0033] Figure 2 This is an appearance diagram of the lightweight high-strength steel alloy part of Example 1;
[0034] Figure 3 This is a metallographic photograph of the surface of a formed sample of the lightweight high-strength steel alloy part of Example 1;
[0035] Figure 4 This is a surface microscopic morphology photograph of the lightweight high-strength steel alloy part of Example 1;
[0036] Figure 5 is the surface roughness of the lightweight high-strength steel alloy part of Example 1;
[0037] Figure 6 This is a structural diagram of the mechanical properties test of the lightweight and high-strength steel alloy parts of Example 1. DETAILED DESCRIPTION
[0038] The present invention is further described below in conjunction with specific implementation methods. It should be noted that, under the premise of no conflict, the various embodiments or technical features described below can be arbitrarily combined to form new embodiments. In the following steps, the specific steps of the plasma rotary atomization method are: using a non-transferred arc rotary electrode atomization device to prepare a low-density steel powder, screening the powder, wherein the smelted rod is placed in an atomization furnace as a positive electrode, filled with argon as a protective gas, and the atomization furnace is evacuated to a vacuum degree of 3×10 - 3 Pa; setting process parameters to start the equipment, so that the rod rotates at high speed, the plasma gun forms a transferred arc to heat and melt one end of the rod, so that the droplets of the melted rod in the atomization chamber are thrown out under the action of centrifugal force, the droplets cool and form powder under the action of surface tension, and after the powder making is completed, the high pressure is maintained for 4 hours in the atomization furnace, and the powder is sieved after cooling and vacuum packaged to obtain spherical powder; wherein the rod rotation speed is 25000r / min, the current of the plasma gun is 2000A, the rod feeding speed is 1.8mm / s, and the distance between the plasma gun and the alloy rod is 30mm.
[0039] Example 1
[0040] A lightweight high-strength steel composition includes the following components in mass fractions: Mn: 28.28wt%; Al: 9.39wt%; C: 1.00wt%, Ni: 3.28wt%; and the rest is Fe.
[0041] The preparation steps are:
[0042] S1: Prepare raw materials according to the designed ratio;
[0043] S2: High-quality light-weight high-strength steel alloy powder is produced by vacuum melting-plasma rotary atomization technology. The light-weight high-strength steel alloy powder with the particle size required for SLM is obtained by sieving. The particle size is 35 μm, and there is no hollow powder satellite powder, such as Figure 1shown.
[0044] S3: After optimizing the selective laser process parameters, 3D printing is performed by the selective laser melting forming equipment to obtain a highly dense, crack-free, deposited SLM lightweight high-strength steel alloy part; the specific steps for optimizing the selective laser melting process parameters are as follows:
[0045] (1) Dry the powder before printing in a vacuum drying oven at 80°C for 5 hours.
[0046] (2) Before printing, inert gas (high-purity argon) is introduced into the molding chamber, and the oxygen concentration reaches 200ppm.
[0047] (3) Raise the substrate temperature to 200°C before printing.
[0048] (4) During printing, the enhanced parameters were set, and the first two layers were scanned twice each, and each layer thereafter was scanned once for selective laser melting printing; the process parameters for selective laser melting were: laser power: 100 W; scanning speed: 800 mm / s; scanning spacing: 75 μm; powder thickness: 20 μm; and the scanning strategy was checkerboard scanning.
[0049] S4: Stress relief annealing is performed on the deposited SLM lightweight high-strength steel parts to obtain SLM lightweight high-strength steel alloy parts with high strength and plasticity. The stress relief annealing is: at 550°C, keep warm for 4 hours, and cool in the furnace.
[0050] The appearance of the SLM lightweight high-strength steel alloy part is as follows Figure 2 shown.
[0051] Test its performance, such as Figure 3-Figure 6 According to tests, the finished product of the present invention has a relative density of up to 99.6%, a Vickers hardness of up to 280Hv, a tensile strength of up to 1100MPa, a yield strength of up to 850MPa, and an elongation after fracture of more than 35%.
[0052] Example 2
[0053] A lightweight high-strength steel composition includes the following components in mass fraction: Mn: 28.28wt%; Al: 9.39wt%; C: 1.00wt%, Ni: 3.28wt%; Cr: 0.54wt%; O: 0.019wt%; P: 0.010wt%; S: 0.0047wt%; Si: 0.088wt%; N: 0.0018wt%; and the rest is Fe.
[0054] The preparation steps are the same as those in Example 1. According to tests, the finished product of the present invention has a relative density of 99.6%, a Vickers hardness of 280 Hv, a tensile strength of 1100 MPa, a yield strength of 850 MPa, and an elongation after fracture of more than 35%.
[0055] Example 3
[0056] A lightweight high-strength steel composition includes the following components in mass fractions: Mn: 28.13wt%; Al: 9.30wt%; C: 0.94wt%, Ni: 3.25wt%; and the rest is Fe.
[0057] The preparation steps are the same as those in Example 1. According to tests, the finished product of the present invention has a relative density of 99.6%, a Vickers hardness of 280 Hv, a tensile strength of 1100 MPa, a yield strength of 850 MPa, and an elongation after fracture of more than 35%.
[0058] Example 4
[0059] A lightweight high-strength steel composition includes the following components in mass fraction: Mn: 28.13wt%; Al: 9.30wt%; C: 0.94wt%, Ni: 3.25wt%; Cr: 0.52wt%; O≤0.017wt%; and the rest is Fe.
[0060] The preparation steps are the same as those in Example 1. According to tests, the finished product of the present invention has a relative density of 99.6%, a Vickers hardness of 280 Hv, a tensile strength of 1100 MPa, a yield strength of 850 MPa, and an elongation after fracture of more than 35%.
[0061] The above-mentioned embodiments are only preferred embodiments of the present invention and cannot be used to limit the scope of protection of the present invention. Any non-substantial changes and substitutions made by technicians in this field on the basis of the present invention shall fall within the scope of protection required by the present invention.
Claims
1. A Fe-Mn-Al-C series lightweight high-strength steel, characterized in that: The following components are included in percentage by mass: Mn 27-30wt%; Al 8.0-10.0wt%; C 0.9-1.2wt%; Ni 3.25-3.28wt%; the rest is Fe; The properties of the Fe-Mn-Al-C series lightweight high-strength steel are as follows: the density of the formed part is 99.6%, there is no crack defect, the Vickers hardness can reach 280Hv, the tensile strength can reach 1100MPa, the yield strength can reach 850MPa, and the elongation after fracture exceeds 35%; Among them, the Fe-Mn-Al-C series lightweight high-strength steel is prepared by selective laser melting preparation technology; Specifically, the preparation steps of the Fe-Mn-Al-C series lightweight high-strength steel are as follows: S1: Prepare raw materials according to the designed ratio; S2: High-quality light-weight high-strength steel alloy powder is produced by vacuum melting-plasma rotary atomization technology, and the light-weight high-strength steel alloy powder with the particle size required for SLM is obtained by screening; the particle size of the light-weight high-strength steel alloy powder with the particle size required for SLM is between 15-53μm, and there is no hollow powder satellite powder; S3: After optimizing the selective laser melting process parameters, 3D printing is performed by the selective laser melting forming equipment to obtain highly dense, crack-free, deposited SLM lightweight high-strength steel alloy parts; The specific steps for optimizing the process parameters of the selective laser melting are as follows: (1) Dry the powder before printing in a vacuum drying oven for 3-5 hours at a temperature of 75-85°C; (2) Inert gas is introduced into the molding chamber before printing, and the oxygen concentration is below 300 ppm; (3) Raise the substrate temperature to 150-200°C before printing; (4) When printing, set the enhanced parameters, scan each of the first two layers twice, and scan each layer once for selective laser melting printing; the process parameters of selective laser melting are: laser power: 90-150W; scanning speed: 600-1000mm / s; scanning spacing: 70-90μm; powder thickness: 20-40μm; scanning strategy is checkerboard scanning; S4: The deposited SLM lightweight high-strength steel parts are subjected to stress relief annealing. The specific operation of stress relief annealing is: at 500℃-600℃, keep warm for 2-6h, furnace cool, and obtain SLM lightweight high-strength steel alloy parts with high strength and plasticity.
2. The Fe-Mn-Al-C lightweight high-strength steel according to claim 1, characterized in that: The Fe-Mn-Al-C series lightweight high-strength steel includes the following components calculated by mass percentage: Mn 28-29wt%; Al 9.2-9.4wt%; C 0.9-1.0wt%; Ni 3.25-3.28wt%; the rest is Fe.
3. The Fe-Mn-Al-C lightweight high-strength steel according to claim 1, characterized in that: The Fe-Mn-Al-C series lightweight high-strength steel also includes the following components calculated by mass percentage: Cr≤0.54 wt%; O≤0.019 wt%; P≤0.010 wt%; S≤0.0047 wt%; Si≤0.088 wt%; N≤0.0018 wt%.
4. A method for preparing a Fe-Mn-Al-C lightweight high-strength steel according to any one of claims 1 to 3, characterized in that: The method comprises the following preparation steps: S1: Prepare raw materials according to the designed ratio; S2: High-quality light-weight high-strength steel alloy powder is produced by vacuum melting-plasma rotary atomization technology, and the light-weight high-strength steel alloy powder with the particle size required for SLM is obtained by screening; the particle size of the light-weight high-strength steel alloy powder with the particle size required for SLM is between 15-53μm, and there is no hollow powder satellite powder; S3: After optimizing the selective laser melting process parameters, 3D printing is performed by the selective laser melting forming equipment to obtain highly dense, crack-free, deposited SLM lightweight high-strength steel alloy parts; The specific steps for optimizing the process parameters of the selective laser melting are as follows: (1) Dry the powder before printing in a vacuum drying oven for 3-5 hours at a temperature of 75-85°C; (2) Inert gas is introduced into the molding chamber before printing, and the oxygen concentration is below 300 ppm; (3) Raise the substrate temperature to 150-200°C before printing; (4) When printing, set the enhanced parameters, scan each of the first two layers twice, and scan each layer once for selective laser melting printing; the process parameters of selective laser melting are: laser power: 90-150W; scanning speed: 600-1000mm / s; scanning spacing: 70-90μm; powder thickness: 20-40μm; scanning strategy is checkerboard scanning; S4: The deposited SLM lightweight high-strength steel parts are subjected to stress relief annealing. The specific operation of stress relief annealing is: at 500℃-600℃, keep warm for 2-6h, furnace cool, and obtain SLM lightweight high-strength steel alloy parts with high strength and plasticity.
Citation Information
Patent Citations
Method for additive manufacturing of high-density Fe-Mn-Al-C light high-strength steel
CN115595462A
Ultrahigh-strength light steel as well as preparation method and application thereof
CN116426840A